Epimeria (Pseudepimeria) debroyeri d'Acoz & Verheye 2017, sp. nov. - d'Acoz, Cédric d'Udekem; Verheye, Marie L. (Zenodo, 2017)
Epimeria ( Pseudepimeria ) debroyeri sp. nov. urn:lsid:zoobank.org:act: 05C0B30A-F5BD-40C0-A3FC-07DE05BFB375 Figs 265–271 Epimeria pulchra – Coleman 2007: 47, in part, colour plate 2 fig. f, not fig. 24a–b (= E. pulchra ). — Lörz & Coleman 2009: unnumbered photograph on p. 17. — Rauschert & Arntz 2015: 62, pl. 55, unnumbered photograph. non Epimeria pulchra Coleman, 1990a: 166–176, pls 10–16. Etymology The species is dedicated to Claude De Broyer (Royal Belgian Institute of Natural Sciences), who collected the holotype of the species. The name is a genitive. Type material Holotype RV Polarstern cruises: SOUTHERN OCEAN: large ♀, cruise PS14, ANT-VII/4, EPOS leg 3, stn 291 (GSN 14), eastern Weddell Sea, 71°06.1ʹ S, 12°33.5ʹ W to 71°05.9ʹ S, 12°34.8ʹ W, 499–515 m, bottom trawl, 19 Feb. 1989, coll. C. De Broyer (RBINS, INV. 132940). Description ROSTRUM. Long, overreaching tip of peduncle of antenna 1; in lateral view, anteriorly weakly curved in its middle and forming a blunt very obtuse angle with head, ventrally straight, tip abruptly curving downwards; in frontal view, fairly narrow, with weakly convex borders, with subacute tip. EYE. Medium-sized, conical. PEREION–PLEOSOME TOOTH PATTERN. Pereionite 1 with medium-sized broad and blunt-tipped mid-dorsal tooth pointing upwards of which the anterior border is straight and the posterior border is strongly convex, with pair of well-developed, blunt, dorsolateral teeth and pair of small ventrolateral teeth; pereionite 2 much narrower than pereionites 1 and 3, with small narrow blunt-tipped tooth pointing upwards (a bit shorter than mid-dorsal tooth of pereionite 1 and much shorter than mid-dorsal tooth of pereionite 3), with pair of small very blunt dorsolateral teeth, and pair of small ventrolateral teeth; pereionites 3–4 with large, broad and blunt to subangulate mid-dorsal tooth pointing upwards, of which the anterior and the posterior borders are both strongly convex, with pair of medium-sized, low and blunt dorsolateral teeth, and pair of small ventrolateral teeth; pereionites 5–7 with large and broad mid-dorsal tooth pointing upwards, of which the anterior border is strongly convex and the posterior border weakly convex, of which the tip is bluntly angulate to subacute, with pair of medium-sized, low and blunt dorsolateral teeth, and pair of small ventrolateral teeth; pleonites 1–2 with large and broad mid-dorsal tooth pointing upwards, of which the anterior border is strongly convex (with weak median angular discontinuity) and the posterior border nearly straight, of which the tip is subacute, with pair of large subacute dorsolateral teeth (anteriorly preceded by small but sharp denticle); pleonite 3 with very broad medium-sized middorsal tooth pointing upwards, of which the anterior border is convex, the tip broad and subangulate and the posterior border weakly convex, with 5 pairs of dorsolateral teeth. COXAE 1–3. Strongly carinate and distally blunt. COXA 4. Anterodorsal border weakly but distinctly concave; anteroventral border with proximal very distinct notch forming an obtuse angle, with distal part convex; anterior angle rounded to very bluntly angulate and projecting forward; ventral tooth long, narrow and acute, directed backwards; lateral carina with rounded to very bluntly angulate lobe strongly projecting laterally, posteriorly followed by fairly shallow rounded concavity, and more backwards by a second, very low lobe projecting laterally; in lateral view, inner corner of carina forming a distinct obtuse (nearly squared) angle; in lateral view posteroventral border of coxa deeply concave, the deepest point of this concavity forming a blunt squared angle (more anteriorly and more distally the posterior border is nearly straight). COXA 5. In dorsal view, with very long, triangular, carinate, lateral tooth, of which the anterior border points obliquely strongly backwards and the posterior border is also distinctly pointing backwards); tip of carina blunt. COXA 6. With triangular carinate lateral tooth of which the anterior border points obliquely backwards and the posterior border is nearly perpendicular to body axis (very weakly pointing onwards) (character to be examined in dorsal view); tip of carina subacute. COXA 7. With ventral border distinctly curved, with posterior border straight, these two borders being joined by a broad curve. EPIMERAL PLATES 1–3. Plate 1 with posteroventral angle broadly rounded, with distinct lateral carina and 1 lateral tooth; plate 2 with posteroventral angle sharply angulate (forming a sharp tooth in squared angle), with distinct lateral carina and 1 lateral tooth; plate 3 with posteroventral angle produced into a long tooth, with distinct lateral carina and 1 lateral tooth, with posterior margin very strongly convex. UROSOME TOOTH PATTERN. Urosomite 1 with sharp narrow tooth pointing upwards, anteriorly preceded by pair of denticles; urosomite 2 with pair of mid-sized posterior dorsolateral teeth pointing upwards; urosomite 3 with pair of mid-sized posterior dorsolateral teeth pointing obliquely backwards. TELSON. Cleft on 0.2; tips of lobes subacute, notch forming a broad V. PEDUNCLE OF ANTENNA 1. Article 1 with anterior border concave, with strong anterior and posterior tooth; article 2 with strong lateral triangular tooth; article 3 with strong ventral tooth. GNATHOPODS 1–2. Very small, achelate; carpus and propodus of normal slenderness in gnathopod 1 (propodus tapering), extremely narrow in gnathopod 2; dactylus of gnathopod 2 fairly narrow and posteriorly straight. PEREIOPODS 3–4. Merus, carpus and propodus extremely broad and short; dactylus fairly large, strongly curved on both sides, clasping. PEREIOPODS 5–6. Basis of normal width, with posteroproximal process sharply triangular, with posterodistal tooth strong, narrow and sharp; merus, carpus and propodus extremely broad and short; dactylus fairly large, strongly curved on both sides, clasping. PEREIOPOD 7. Basis broad; posterior border parallel to axis of basis in proximal 0.75; at this level it forms a distinct acute (nearly squared) angle, which is followed by a deep concavity; this concavity forms a rounded obtuse (nearly squared) angle; the posterodistal corner is produced into a long narrow tooth pointing obliquely backwards; merus, carpus and propodus extremely broad and short; dactylus fairly large, strongly curved on both sides, clasping. Colour pattern Body and appendages entirely white; eye reddish (Coleman 2007: 47, colour plate 2f; Rauschert & Arntz 2015: 62, pl. 55, both as Epimeria pulchra ). Body length 33 mm. Distribution Eastern shelf of the Weddell Sea, 499– 515 m. Remarks Epimeria debroyeri sp. nov. (eastern shelf of the Weddell Sea) is very similar to E. amoenitas sp. nov. (Adélie Coast). See key and account on E. amoenitas sp. nov. The specimen of E. debroyeri sp. nov. illustrated by a photograph as E. pulchra in Coleman (2007) and reproduced in Rauschert & Arntz (2015) was collected on the eastern shelf of the Weddell Sea. Indeed, in an early draft of Rauschert & Arntz’s (2015) book, it was indicated that this specimen was collected during the cruise ANT-XIII/3 dedicated to the study of that region. : Published as part of d'Acoz, Cédric d'Udekem & Verheye, Marie L., 2017, Epimeria of the Southern Ocean with notes on their relatives (Crustacea, Amphipoda, Eusiroidea), pp. 1-553 in European Journal of Taxonomy 359 on pages 126-129, DOI: 10.5852/ejt.2017.359, http://zenodo.org/record/3855694 : {"references": ["Coleman C. O. 2007. Synopsis of the Amphipoda of the Southern Ocean. Volume 2: Acanthonotozomellidae, Amathillopsidae, Dikwidae, Epimeriidae, Iphimediidae, Ochlesidae and Vicmusiidae. Bullelin de l'Institut Royal des Sciences Naturelles de Belgique, Biologie / Bulletin van het Koninklijk Belgisch Instituut voor Natuurwetenschappen, Biologie 77, supplement 2: 1 - 134.", "Lorz A. - N. & Coleman O. 2009. Living gems: jewel-like creatures from the deep. Water & Atmosphere 17 (1): 16 - 17. Available from https: // www. niwa. co. nz / sites / niwa. co. nz / files / import / attachments / gems. pdf [accessed 27 Sep. 2016].", "Rauschert M. & Arntz W. E. 2015. Antarctic Macrobenthos. A Field Guide of the Invertebrates Living at the Antarctic Seafloor: Arntz & Rauschert Selbstverlag, Deichweg.", "Coleman C. O. 1990 a. Two new Antarctic species of the genus Epimeria (Crustacea: Amphipoda: Paramphithoidae), with description of juveniles. Journal of the Royal Society of New Zealand 20 (2): 151 - 178. https: // doi. org / 10.1080 / 03036758.1990.10426723"]}